Prevalence of USA300 Colonization or Infection and Associated Variables During an Outbreak of Community-Associated Methicillin-Resistant Staphylococcus aureus in a Marginalized Urban Population. Issue 6 (2007) - Gilbert, Mark; MacDonald, Judy; Louie, Marie; Gregson, Dan; Zhang, Kunyan; Elsayed, Sameer; Laupland, Kevin; Nielsen, Diane; Wheeler, Virginia; Lye, Tara; Conly, John
Abstract : BACKGROUND: In 2004, an outbreak of the USA300 strain of methicillin-resistant Staphylococcus aureus (MRSA) was identified in persons with histories of homelessness, illicit drug use or incarceration in the Calgary Health Region (Calgary, Alberta). A prevalence study was conducted to test the hypotheses for factors associated with USA300 colonization or infection. METHODS: Participants were recruited at sites accessed by this marginalized population. Health care staff administered a questionnaire and collected crack pipes and nasal, axillary and skin infection swabs. Pipes and swabs were cultured according to standard techniques. MRSA isolates were further characterized by polymerase chain reaction ( mecA, Panton-Valentine leukocidin and Staphylococcal cassette chromosome mec ) and typing methods (pulsed-field gel electrophoresis, staphylococcal protein A typing and multilocus sequence typing). Colonization or infection was determined by having any one of nasal, axillary, skin infection or pipe swabs positive for USA300. Colonized participants had one or more nasal, axillary or pipe swab positive for USA300; infected participants had one or more skin infection swab positive for USA300. RESULTS: The prevalence of USA300 colonization or infection among 271 participants was 5.5% (range 3.1% to 9.0%). USA300 cases were more likely to report manipulation of skin infections (OR 9.55; 95% CI 2.74 to 33.26); use of crack pipes was not significant despite identification of the USA300 strain on two of four crack pipes tested. USA300 cases were more likely to report drug use between sex trade workers and clients (OR 5.86; 95% CI 1.63 to 21.00), and with casual sex partners (OR 5.40; 95% CI 1.64 to 17.78). CONCLUSION: Ongoing efforts to promote the appropriate treatment of skin infections in this population are warranted. The association of USA300 colonization or infection and drug use with sexual partners suggest a role for sexual transmission of the USA300 strain of MRSA.